Exploring “linguistic complementarity” for intercultural communication in postcolonial African states - Oyekunle, Akinpelu Ayokunnu (Frontiers in Communication, 2025)
This paper explores the concept of linguistic complementarity as a philosophical framework for intercultural communication in postcolonial African contexts. As a conceptual research paper, the study explores the idea of linguistic complementarity to highlight the significance of cultural diversity in fostering effective communication and mutual understanding. The paper argues that linguistic complementarity provides a panacea to the “language question” in postcolonial African society and, by extension, African philosophy. The paper also explores the advantages and difficulties associated with the application of linguistic complementarity in postcolonial Africa, as well as its implementation in education, government, and the media. The conclusion emphasises the importance of promoting intercultural dialogue and understanding through linguistic complementarity and recommends further research and implementation of linguistic complementarity in intercultural communication.